Environmental Knowledge, Race, and African American Literature - Klestil, Matthias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This open access book suggests new ways of reading nineteenth-century African American literature environmentally. Combining insights from ecocriticism, African American studies, and Foucauldian theory, Matthias Klestil examines forms of environmental knowledge in African American writing ranging from antebellum slave narratives and pamphlets to Charlotte Forten$1 (Bs journals, Booker T. Washington$1 (Bs autobiographies, and Charles W. Chesnutt$1 (Bs short fiction. The volume highlights how literary forms of environmental knowledge in the African American tradition were shaped by the histories of slavery and race, mainstream environmental writing traditions, and African American forms of expression and intertextuality. Turning to the Underground Railroad, debates over education and home-building, and the aesthetics of the pastoral and the georgic, Environmental Knowledge, Race, and African American Literature provides an original perspective on the African American ecoliterarytradition that uncovers new facets of canonical and understudied texts and offers new directions for ecocriticism and African American studies.s
1. Introduction: African American Environmental Knowledge at Niagara -- Part I Foundations: Antebellum African American Environmental Knowledge -- 2. Claiming (through) Space: Topographies of Enslavement, the Literary Heterotopia of the Underground Railroad, and the Co-Agency of the Non-human -- 3. Resisting (through) the Eye: Antebellum Visual Regimes, the Slave Narrative$1 (Bs Rhetoric of Visibility, and African American Strategic Pastoral -- 4. Negotiating (through) the Skin: The Black Body, Pamphleteering, and African American Writing against Biological Exclusion -- Part II Transformations: African American Environmental Knowledge from Reconstruction to Modernity -- 5. Transforming Space: Nature, Education, and Home in Charlotte Forten and William Wells Brown -- 6. Transforming Vision: The Pastoral, the Georgic, and Evolutionary Thought in Booker T. Washington -- 7. Transforming the Politics of the Black Body: Trans-corporeality, Epistemological Resistance, and Spencerism in Charles W. Chesnutt -- 8. Conclusion: African American Environmental Knowledge at Yellowstone.s
Keywords: America -- Literatures; Literature, Modern -- 19th century; Ecocriticism; African Americans; Culture; Human ecology -- History; Race; North American Literature; Nineteenth-Century Literature; Ecocriticism; African American Culture; Environmental History; Race and Ethnicity Studies